Pengaruh Diskon Harga dan Promo Bundling Terhadap Keputusan Pembelian Toko Kacamata XYZ di Sukoharjo - Dewi Septyasari; Ari Susanti (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of price discounts and promotional bundling on consumer purchase decisions at XYZ Optical Store in Sukoharjo. The research adopts a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 96 respondents selected using accidental sampling. Data analysis was conducted using multiple linear regression with SPSS software. The results indicate that price discounts do not have a positive and significant effect on purchase decisions, while promotional bundling has a positive and significant influence on consumer purchase decisions. These findings suggest that for high-involvement products such as eyeglasses, consumers tend to prioritize functional value, quality, and perceived benefits rather than short-term price reductions. Theoretically, this study strengthens consumer behavior theory and the concept of value-based promotion, emphasizing the role of perceived value in purchase decision-making. Practically, the findings provide important insights for optical retail businesses to focus more on promotional bundling strategies rather than relying solely on price discounts to stimulate purchases. This study contributes empirical evidence to the retail marketing literature, particularly in the context of the optical industry, and offers directions for developing more effective and sustainable promotional strategies.